Case Report: When genetic diagnosis comes late: lessons from a DEND syndrome patient successfully transitioned to sulfonylurea - Abreu, Gabriella de Medeiros; Bastos de Souza, Ritiele; Bernardo, Marília Chaves; da Cruz Junior, Jardeson Lima; Ferreira, Amanda; Snaider, Deborah; da Fonseca, Ana Carolina Proença; Salum, Kaio Cezar Rodrigues; Zembrzuski, Verônica Marques; Lima, Marco Antonio; Tarantino, Roberta Magalhães; Rodacki, Melanie; et al. (Frontiers in Clinical Diabetes and Healthcare, 2025)
Neonatal diabetes mellitus (NDM) is a rare cause of diabetes characterized by the presence of severe hyperglycemia typically diagnosed within the first six months of life. Among the main causes are activating variants in heterozygosity in the KCNJ11 gene. Variants in this gene can lead to a spectrum of clinical manifestations, from transitory neonatal diabetes mellitus to DEND syndrome, the most severe form, characterized by developmental delay, epilepsy, neonatal diabetes, and muscle hypotonia. The disease may be present in a milder intermediate form named iDEND syndrome. Patients with KCNJ11 variants may present with attention deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD), developmental coordination disorder (DCD), and learning difficulties due to diminished intelligence quotient (IQ) and dyslexia. These patients can benefit from genetic counseling as most of them can switch from insulin to sulfonylurea treatment with good glycemic control and no severe side effects; besides, some studies report a neurological improvement after the treatment switch. In the present work, we reported a follow-up of a 24-year-old Brazilian male with DEND syndrome due to the KCNJ11 c.754G>A; p.(Val252Met) variant. He was diagnosed with diabetes at 25 days of age and presented with bilateral hypoacusis in the first years of life. He started insulin at the diagnosis. However, the genetic diagnosis was made only at the age of 15 years, and he was switched from insulin to sulfonylurea. At 24 years of age, he presents with good glycemic control and reports no severe episodes of hypoglycemia or hyperglycemia. However, no neurological improvement was observed. This report highlights the potential benefits of switching to sulfonylurea treatment, even in patients with long-standing diagnoses of DEND syndrome, and underscores the importance of genetic diagnosis, as early initiation of sulfonylurea therapy may improve metabolic control and, in some cases, neurological outcomes.